Relationship Of Self-Disclosure With Interpersonal Communication Of High School Teenagers - Ella Ilvana Mutia; Mursyid Ridha (Universitas Negeri Padang, 2019)
Interpersonal communication has an important role to be done with others. Background of this study there are still many students who have poor interpersonal communication skills, such as talking about friends, saying rude to friends, and not empathizing with friends. The purpose of this study is to discuss the significance of the relationship between self-disclosure and interpersonal communication of high school adolescents. This research uses quantitative by using descriptive correlational method. Population of this study were 442 students of Pertiwi 1 Padang High School. The sample was 200 students selected using proportional stratified random sampling. The instrument required is a scale using a Likert scale model. The data obtained were analyzed using descriptive and correlational techniques with the Pearson Product Moment Correlation help computer program SPSS 20.00. Unpublished research findings about self-disclosure with interpersonal communication of high school teenagers at Pertiwi 1 Padang High School.